Incentivizing research & innovation with agrobiodiversity conserved in situ: Possibilities and limitations of a blockchain-based solution. (1st August 2021) - Kochupillai, Mrinalini; Gallersdörfer, Ulrich; Köninger, Julia; Beck, Roman
Abstract: This article explores the use of blockchain for agrobiodiversity (B4A) with a specific focus on (i) providing an overview of the existing regulatory challenges that result in sub-optimal research and innovation with agrobiodiversity conserved in situ, (ii) investigating how a blockchain-based solution may help overcome these challenges, and (iii) illustrating how incentive mechanisms can help to overcome shortcomings in existing intellectual property regimes that prevent effective conservation, research and innovation (CRI). Our research identifies (i) lack of channels for transparent and equitable sharing of know-how and materials (ii) lack of incentives, (iii) lack of trust among stakeholders, and (iv) lack of traceability options as main hindering reasons for in situ CRI with agrobiodiversity. Further, we find that blockchain solutions may empower data providers, including small farmers, to collectively track, control and monetize the use of data and assets shared while minimizing fraudulent activities. Transaction costs may also be lowered by removing complex and expensive interaction processes. However, further research and development are necessary to design an ethical and sustainable blockchain-based solution to incentivize in situ conservation, research and innovation with agrobiodiversity. Some future directions of research are recommended.